AN ANALYSIS OF ISLAMIC BUSINESS ETHICS IN BALLS PRODUCT MARKETING AT LEMBUR SAWAH VILLAGE IN THE COVID 19 PANDEMIC ERA - AYU SONIA; ERRY SUNARYA; ACEP SAMSUDIN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Currently we are experiencing a COVID-19 pandemic condition which causes business actors to market products online, but online marketing, many consumers are dissatisfied with the goods sent because of the incompatibility of the goods described with the goods sent, this is related to deviations in business ethics. The purpose of this study was to determine the implementation of Islamic business ethics, the implementation of marketing strategies, and the relationship between the implementation of Islamic business ethics and marketing strategies for ball producers in the village of Lembur Sawah. This research method is a descriptive study using a qualitative approach. The processing process goes through three stages, namely data reduction, data presentation, and drawing conclusions. The validity technique used by the researcher is triangulation. There are source triangulation, technique triangulation, and time triangulation. The research conducted by the author is a ball producer in the village of Overtime Sawah. The results showed that the application of Islamic business ethics to the marketing mix marketing strategy for ball producers in Lembur Sawah village was good, namely product strategy, price strategy, distribution/place strategy and promotion strategy seen from the perspective of Islamic business ethics and also ethical theory. Islamic business according to Muhammad Djakfar (2007:85) is appropriate.